2004
DOI: 10.1161/01.str.0000106484.62689.45
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Inflammatory and Hemostatic Parameters, Atherosclerotic Risk Factors, and Chest X-Ray for Aortic Arch Atheromatosis

Abstract: Background and Purpose-Aortic arch atheromatosis (AAA) is a common cause of cerebral embolism. Transesophageal echocardiography (TEE) shows not only the extension of atherosclerotic plaques but also the mobility of superimposed thrombi. In most cases AAA is only detected after the embolic event. This study was therefore designed to identify predictive factors for AAA. Methods-One hundred seven consecutive patients referred for routine TEE were included in the study. Patients on warfarin therapy, with a history… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 35 publications
2
8
0
Order By: Relevance
“…19 Ehlermann et al showed an association of severe aortic atheromatosis and elevated levels of fibrinogen, PIC, and D-dimer; however the subjects were not limited to AF patients. 20 Our results are consistent with those of Ehlermann et al 20 in that the coexistence of severe atherosclerosis with AF would synergistically lead to hypercoagulable state. In contrast to the results of Feinberg et al, 19 we showed an association of severe atheroma with activation of coagulation but not with activation of platelet function.…”
Section: Aortic Atheroma As Thromboembolic Risk In Af Patientssupporting
confidence: 92%
See 1 more Smart Citation
“…19 Ehlermann et al showed an association of severe aortic atheromatosis and elevated levels of fibrinogen, PIC, and D-dimer; however the subjects were not limited to AF patients. 20 Our results are consistent with those of Ehlermann et al 20 in that the coexistence of severe atherosclerosis with AF would synergistically lead to hypercoagulable state. In contrast to the results of Feinberg et al, 19 we showed an association of severe atheroma with activation of coagulation but not with activation of platelet function.…”
Section: Aortic Atheroma As Thromboembolic Risk In Af Patientssupporting
confidence: 92%
“…11 There have been other studies to determine the association of increased plasma levels of hemostatic markers with systemic atherosclerosis. 19,20 Feinberg et al showed an association of elevated levels of F1+2 and clinical risk factor for stroke, and a relation between -TG and atherosclerosis in patients with nonrheumatic AF of SPAF-III study; however, TEE findings were not analyzed in their study. 19 Ehlermann et al showed an association of severe aortic atheromatosis and elevated levels of fibrinogen, PIC, and D-dimer; however the subjects were not limited to AF patients.…”
Section: Aortic Atheroma As Thromboembolic Risk In Af Patientsmentioning
confidence: 92%
“…Previous studies identified the characteristics of patients who had advanced AAPs but not MAPs, which include older age, the presence of risk factors for atherosclerosis, and concomitant vascular diseases such as coronary artery disease. 27,28 Moreover, the presence of AAPs was found to have a sensitivity of 90% and a specificity of 90% for coronary artery obstruction and could be used as a predictor of cardiovascular events. 28,29 Multiple brain infarctions have been frequently observed in patients with acute ischemic stroke, especially in patients with cardiac embolic sources such as atrial fibrillation, intracardiac thrombus, and even patent foramen ovale.…”
Section: Discussionmentioning
confidence: 99%
“…The aortic atherosclerosis is important, mainly because of its relation to coronary and carotid atherosclerosis, and to cerebral and peripheral embolism (14,15). It has been reported that plasma fibrinogen (16); homocysteine (17); C-reactive protein (18); high-density lipoprotein (19); lipoprotein (a) (20) and coagulation parameters such as D-dimers, activated factor II, prothrombin fragments 1 and 2; and plasmin/antiplasmin complexes (14) levels and leukocyte count (21) have been related to the thoracic aorta atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%